Vasopressin in Hemorrhagic Shock: A Systematic Review and Meta-Analysis of Randomized Animal Trials. (1st September 2014) - Cossu, Andrea Pasquale; Mura, Paolo; De Giudici, Lorenzo Matteo; Puddu, Daniela; Pasin, Laura; Evangelista, Maurizio; Xanthos, Theodoros; Musu, Mario; Finco, Gabriele
Abstract : Objective. The latest European guidelines for the management of hemorrhagic shock suggest the use of vasopressors (norepinephrine) in order to restore an adequate mean arterial pressure when fluid resuscitation therapy fails to restore blood pressure. The administration of arginine vasopressin (AVP), or its analogue terlipressin, has been proposed as an alternative treatment in the early stages of hypovolemic shock. Design. A meta-analysis of randomized controlled animal trials. Participants. A total of 433 animals from 15 studies were included. Interventions. The ability of AVP and terlipressin to reduce mortality when compared with fluid resuscitation therapy, other vasopressors (norepinephrine or epinephrine), or placebo was investigated. Measurements and Main Results. Pooled estimates showed that AVP and terlipressin consistently and significantly improve survival in hemorrhagic shock (mortality: 26/174 (15%) in the AVP group versus 164/259 (63%) in the control arms; OR = 0.09 ; 95% CI 0.05 to 0.15; P for effect < 0.001; P for heterogeneity = 0.30; I 2 = 14 % ). Conclusions. Results suggest that AVP and terlipressin improve survival in the early phases of animal models of hemorrhagic shock. Vasopressin seems to be more effective than all other treatments, including other vasopressor drugs. These results need to be confirmed by human clinical trials.